Forkalkninger i hjerteklaffer hos atlantisk laks (Salmo salar) - Erkinharju, Toni; Bornø, Geir; Furnesvik, Lisa; Hansen, Miroslava (Den norske veterinærforening / Norwegian Veterinary Association, 2019)
Journal home page at https://nvt.vetnett.no/ .